Évaluation préliminaire de l’effet in vitro de l’entomopathogène autochtone Beauveria sp. (Hypocreales: Clavicipitaceae) sur les larves du ver blanc - SEBIH, Hocine (My University, 2018)
White grubs are natural enemies of crops. The losses caused by the latter are important, which led to the development of many control methods. The present study aims to propose an alternative solution based on the use of indigenous entomopathogens to control these pests. The main objective of our work is to evaluate in vitro the insecticidal effect of the entomopathogenic fungus Beauveria sp. On whiteworm larvae in presence and absence of soil. Then a preliminary identification of phytophage based on the morphology of larvae and adults was carried out. The results obtained show that under the effect of the same concentration of Beauveria sp. The morbidity of the larvae is influenced by the soil. In fact, only 33.33% of the larvae were eliminated in the lot containing soil, while for larvae exposed directly to the effect of the fungus, a maximum of 80% of mortality was recorded. After the identification of the pest, it turned out that the species studied is probably Phyllognathus sp.
Keywords: Effet larvicide; Beauveria sp; ver blanc; identification; Phyllognathus sp.; Larvicide effect; white grub